Seller Strategies to Increase Clothing Sales During Ramadan at Tanah Abang Market, Jakarta - Nada Sariningsih; Siti Halimatussadiah; Sri Damayanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
The month of Ramadan, a religious and cultural event in Indonesia, is closely linked to the tradition of buying new clothes to celebrate Eid al-Fitr. This tradition has evolved into a socio-economic phenomenon that drives increased public consumption and trade activity each year. This condition makes Tanah Abang Market one of the centers of economic activity, experiencing a significant surge in demand. The urgency of this research lies in the importance of understanding how traders are able to survive and compete amidst the high intensity of competition during the Ramadan period. Without the right strategy, traders risk losing competitiveness despite increasing market opportunities. Therefore, this study aims to analyze the sales strategies used by traders to increase consumer purchasing power and sales volume. This study uses a descriptive qualitative approach with a literature study method. Data were collected from various literature sources, such as academic books, scientific journal articles, previous research, and official publications from relevant institutions such as the Central Bureau of Statistics. The data obtained were analyzed using qualitative analysis techniques through a process of classification, interpretation, and critical analysis to identify relevant patterns and strategies. The results show that traders implement strategies such as following fashion trends, creating innovative product designs, offering discounts, and utilizing reseller networks to expand distribution. This strategy has proven to be able to increase sales, expand market reach, and strengthen consumer loyalty as well as optimize existing capital to maintain competitiveness in traditional markets.